The tachyon potential in the sliver frame - Arroyo, E. Aldo [UNESP] (Int School Advanced Studies, 2009)
We evaluate the tachyon potential in the Schnabl gauge through off-shell computations in the sliver frame. As an application of the results of our computations, we provide a strong evidence that Schnabl's analytic solution for tachyon condensation in open string field theory represents a saddle point configuration of the full tachyon potential. Additionally we verify that Schnabl's analytic solution lies on the minimum of the effective tachyon potential.
Keywords: Tachyon Condensation; String Field Theory